Lens in the Classroom: Ideas to Use Camera Traps in an Educational Setting - Kathleen A. Carey; Brandon W. McDonald; Annesha Lahiri; Brittany M. Mason; Isaac L. Esquivel; Corey T. Callaghan; Carolina Baruzzi (EDIS, 2025)
This publication provides some examples of effectively using camera traps to teach ecological concepts related to wildlife feeding preferences, daily activity, human disturbance, ecosystem engineering, and pollinators. Written by K. A. Carey, B. W. McDonald, A. Lahiri, B. M. Mason, I. L. Esquivel, C. T. Callaghan, and C. Baruzzi, and published by the UF/IFAS Department of Wildlife Ecology and Conservation, June 2025.